EFFECT OF THE PROCESSING ON SOME CHEMICAL COMPONENTS OF PINEAPPLE TROPICAL JUICE - Maia, Geraldo A.; Fernandes, Aline G.; Santos, Gerusa M.; Silva, Daniele S.; Sousa, Paulo H. M. de; Brasil, Isabella M.; Fonseca, Ana V. V. (Revista Brasileira de Engenharia de Biossistemas, 2007)
The chemical and physicochemical changes during the tropical pineapple juice processing were evaluated. It was verified that all the chemical and physicochemical parameters evaluated showed a statistical difference at a level of 5% of probability by the Tukey test, exception for carotenoid content. Total titratable acidity, reducing sugar and carotenoid content increased during the processing. The pH, total soluble solids (Brix), total sugars and anthocyanins content did not differed statistically among formulation/homogenation and after thermal treatment phases. The results suggested that processing phases such as extraction, formulation/homogenation and thermal treatment had a significant effect on the chemical and physicochemical characteristics of the tropical pineapple juice.